"I Still Love My Hood": Passive and Strategic Aspects of Role Residual Among Former Gang Members. (June 2021) - Bubolz, Bryan F.; Lee, Sou
One important aspect of gang disengagement that has been largely overlooked is the role of identity in the time following membership. Research has shown that former gang members often retain social and emotional ties with their former gang peers and may experience role ambiguity as a result. Despite this, there has been virtually no examination of role residual—the lingering aspects of one's former identity—that may exist among these individuals. Using life history interviews, the current study addresses this gap by examining role residual among a sample of 30 former gang members. A total of 25 participants (83%) identified three types of role residual—symbolic, demeanor, and worldview. In contrast to previous scholarship, role residual appeared to manifest as passive and strategic occurrences.